Biofilms and Veterinary Medicine - Percival, Steven L.; Percival, Steven L.; Knottenbelt, Derek C.; Knottenbelt, Derek C.; Cochrane, Christine A.; Cochrane, Christine A. (Springer Series on Biofilms,, 2011)
Biofilms are implicated in many common medical problems including urinary tract infections, catheter infections, middle-ear infections, dental plaque, gingivitis, and some less common but more lethal processes such as endocarditis and infections in cystic fibrosis.  However, the true importance of biofilms in the overall process of disease pathogenesis has only recently been recognized. Bacterial biofilms are one of the fundamental reasons for incipient wound healing failure in that they may impair natural cutaneous wound healing and reduce topical antimicrobial efficiency in infected skin wounds.  Their existence explains many of the enigmas of microbial infection and a better grasp of the process may well serve to establish a different approach to infection control and management.   Biofilms and their associated complications have been found to be involved in up to 80% of all infections.  A large number of studies targeted at the bacterial biofilms have been conducted, and many of them are referred to in this book, which is the first of its kind.   These clinical observations emphasize the importance of biofilm formation to both superficial and systemic infections, and the inability of current antimicrobial therapies to ‘cure’ the resulting diseases even when the in vitro tests suggest that they should be fully effective. In veterinary medicine the concept of biofilms and their role in the pathogenesis of disease has lagged seriously behind that in human medicine.  This is all the more extraordinary when one considers that much of the research has been carried out using veterinary species in experimental situations.   The clinical features of biofilms in human medicine is certainly mimicked in the veterinary species but there is an inherent and highly regrettable indifference to the failure of antimicrobial therapy in many veterinary disease situations, and this is probably at its most retrograde in veterinary wound management.  Biofilms and Veterinary Medicine is specifically focused on discussing the concerns of biofilms to health and disease in animals and provides a definitive text for veterinary practitioners, medical and veterinary students, and researchers.